Kajian Sara dalam Mewujudkan Good Governance di Bidang Administrasi Perpajakan - Selvi Selvi; Maya Puspita Dewi; Agitta Sofyan Purwaningtyas (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2021)
SARA in Manifesting Tax Administration Good Governance. Low tax compliance means that tax revenue has not been able to reach the target. One of the causes is the lack of resources and authority possessed by the Directorate General of Taxes. This research is to analyze Semi- Autonomous Revenue Agencies (SARA) in manifesting good governance. This study uses a qualitative approach with data collection techniques in the form of observation, interviews and using secondary data. The results show that SARA will give more authority to tax authorities in terms of resource management, policy formulation and decision making so that in some countries SARA has succeeded in increasing tax revenue. However, SARA is also prone to abuse of power, so there is a need for a system to monitor SARA